Nickel-based strip electrode submerged arc sintered flux for nuclear power and preparation method

By adjusting the proportion of metal elements and alkaline oxides, adding alloy elements, and using high-grade raw materials and high-model sodium silicate, the problem of insufficient welding process and mechanical properties of existing nickel-based flux in welding nuclear power equipment is solved, and the problem of insufficient welding process and mechanical properties of existing nickel-based flux in welding is achieved. High-quality forming of welds and improved corrosion resistance.

CN119159281APending Publication Date: 2024-12-20BEIJING JINWEI WELDING MATERIAL +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411657529.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

The existing nickel baseband submerged arc flux is difficult to meet the welding process performance and mechanical properties in the welding of nuclear power equipment, and is prone to defects such as sticky slag, undercuts and thermal cracks.

Method used

A nickel baseband submerged arc sintered flux for nuclear power was designed. By adjusting the ratio of metal elements and alkaline oxides, controlling the melting point, density and viscosity, adding alloy elements to strengthen the weld, using high-grade raw materials and 2:1 high Model sodium silicate is used as a binder to dry mixing, wet mixing, granulation, low-temperature drying and high-temperature sintering.

Benefits of technology

The welding process performance has been improved, the weld metal forming is beautiful, the edge transition is smooth, the chemical composition is stable, the corrosion resistance is strong, the mechanical properties meet the usage requirements, and the possibility of thermal cracks is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention relates to a nickel-based strip electrode submerged arc sintered flux for nuclear power and a preparation method thereof. The flux is prepared from the following dry powder components and a binder sodium potassium silicate in parts by weight: 50-60 parts of fluorite, 10-20 parts of sillimanite, 10-20 parts of magnesia, 5-10 parts of wollastonite, 5-10 parts of chrome green, 1-5 parts of aluminum-magnesium alloy, 1-5 parts of niobium-nickel alloy, 1-3 parts of manganese metal and 20-25 parts of sodium potassium silicate. The flux can be used for surfacing of the surface of a pressurized water reactor steam generator in a nuclear power station.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of welding materials, and specifically relates to a nickel-based strip-electrode submerged arc sintering flux for nuclear power. The flux can be used for surfacing welding on the surface of a pressurized water reactor steam generator inside a nuclear power plant. The invention also relates to a method for preparing the flux. Background Art

[0004] There are some nickel-based submerged arc sintering fluxes disclosed in the prior art. For example, CN105215576A (application number: 201510607720.9, Will) provides a nickel-based submerged arc surfacing sintering flux and a manufacturing method. The weight ratio composition is CaF2: 25-50%, SiO2: 5-20%, Al2O3: 10-40%, CaO: 8-20%, MgO: 4-15% and Cr2O3: 0-5%. The flux mineral powder is sieved through 100 mesh, the metal powder is sieved through 40 mesh, put into a container for full dry mixing, 10-30% water glass is added for wet mixing, and then put into a granulator for granulation. After granulation, it is sintered at high temperature in an electric furnace to eliminate the moisture and crystal water of the flux. The sintering temperature is 780±30℃, and it is cooled out of the furnace and sieved into a sintering flux of 10-60 mesh. It is believed that the nickel-based submerged arc cladding flux involved in the invention, matched with nickel-based high Mn and high Nb welding strip, is suitable for cladding of important structural parts such as reactor pressure vessels and steam generator tube plates. It has excellent slag removal performance, good weld bead spreading, and no undercut phenomenon.

[0005] CN105252172A (application number: 201510629296.8, Shuangrui) discloses a method for preparing a sintered flux for nickel-based strip-electrode submerged arc cladding. The sintered flux contains fluorite, marble, α-alumina, zircon sand, sodium fluoride, pure potassium water glass and alloy powder, wherein the fluorite, marble and α-alumina constitute an alkaline slag system, the nickel-based strip is an EQNiCrMo-3 welding strip, and the EQNiCrMo-3 welding strip is used together with the sintered flux. The method is characterized in that the sintered flux is mixed in the following proportions by weight: 38-48 parts of fluorite, 1-5 parts of marble, and 28-34 parts of α-alumina. 1~4 parts of zircon sand, 1~3 parts of sodium fluoride, 17~21 parts of pure potassium water glass, 1~2 parts of alloy powder; the wt% content requirements of the above fluorite CaF2 are: CaF2≥97.0, SiO2≤1.00, S≤0.010, P≤0.010, and the particle size of fluorite CaF2 is required to be 80 mesh; the wt% content requirements of the above marble CaCO3 are: CaCO3≥99, S≤0.010, P≤0.010, and the particle size of marble CaCO3 is required to be 60 mesh; the wt% content requirements of the above α-alumina Al2O3 are: Al2O3≥99, S≤0.030 , P≤0.030, the particle size of α-alumina Al2O3 is required to be 80 mesh; the wt% content requirements of the above zircon sand ZrSiO4 are: ZrO2≥60, SiO2≥32, S≤0.050, P≤0.010, the particle size of zircon sand ZrSiO4 is required to be 80 mesh; the purity requirements of the above sodium fluoride NaF are: NaF≥99.0, the particle size of sodium fluoride NaF is required to be 60 mesh; the wt% content requirements of the above pure potassium water glass are: K2O≥12.6, SiO2≥26.2, S≤0.010, P≤0.010, the modulus of pure potassium water glass is required to be equal to 3. 2. The Baume degree at 20°C is equal to 37~40°Be′; the alloy powder is composed of nickel powder and chromium powder, and the nickel powder: chromium powder = 1:1; according to the above ratio, fluorite, marble, α-alumina, zircon sand, sodium fluoride and alloy powder are dry mixed together and stirred evenly, then pure potassium water glass is added for wet mixing and granulation and stirred evenly, the wet mixing granulation is placed in a drying furnace for low-temperature drying, the temperature of low-temperature drying is controlled at 300°C, and then moved to a high-temperature sintering furnace for high-temperature sintering, the temperature of high-temperature sintering is controlled at 650~700°C, and after high-temperature sintering, it is sieved through 20~100 meshes to prepare a sintering flux. It is believed that the welding processability of the sintering flux is good, matching the corresponding welding strip for welding, the chemical composition of the cladding layer meets the requirements, the intergranular corrosion test results are good, and no cracks are generated in the bending test after corrosion.

[0006] CN106514054A (application number: 201611073244.8, Shuangrui) discloses a sintered flux for nickel-based 625 alloy strip submerged arc surfacing and a preparation method thereof, which relates to the field of welding materials. The sintered flux is sintered by raw materials with the following weight ratio: fluorite: 30-45 parts, alumina: 35-45 parts, zircon sand: 0.5-4 parts, magnesia: 6-10 parts, sodium fluoride: 1-3 parts, chrome green: 1-3 parts, metal manganese: 3-10 parts, and water glass with a total weight of 18-25% of the above powder. The above raw materials are mixed evenly, granulated, first dried at 200-300°C, and then sintered at 350-450°C to obtain a finished flux. It is believed that the flux of the invention has the advantages of low-temperature sintering, easy slag removal, stable arc, weld formation and good corrosion resistance.

[0007] CN104722956A (application number: 201510118024.1, Jinwei) relates to a sintered flux for nickel-based strip-electrode submerged arc welding, which is prepared from dry powder components and a binder, water glass; the dry powder components and their mass percentages are: CaF2 20-50%, Al2O3 20-40%, MgO 10-20%, SiO2 5-10%, CaO 5-15%, sodium fluoride 1-5%, rare earth fluoride 1-5%, and niobium-iron alloy powder 1-5%; the binder water glass has a potassium-sodium ratio of 2:1, a modulus of 2.4-3.5, a Baume degree of 39-45 at room temperature, and an amount of 20-30% of the weight of the dry powder. The sintered flux of the invention can be used in conjunction with a variety of nickel-based welding strips such as EQNiCrMo-3 and EQNiCr-3. When it is used in conjunction with nickel-based welding strips for strip-electrode submerged arc cladding, it can maintain a stable cladding process and excellent welding process performance within a wider range of welding process parameters, and the cladding layer has excellent forming quality. Moreover, various indicators of the cladding layer meet user requirements.

[0008] However, the art still expects a nickel-based submerged arc sintering flux for nuclear power, which is used for the welding of nuclear power main equipment, has good welding process performance during the welding process, the metal of the weld overlay layer has good corrosion resistance, and the mechanical properties fully meet the use requirements. Summary of the invention

[0009] The purpose of the present invention is to design a nickel-based submerged arc sintering flux for nuclear power, which is used for welding of nuclear power main equipment, takes into account welding process performance and mechanical properties, has good welding process performance during welding, stable welding process, good slag removal performance, beautiful metal forming of the cladding layer, smooth overlap transition, stable chemical composition, good corrosion resistance, mechanical properties that fully meet the use requirements and other excellent performances in one or more aspects.

[0010] To this end, the present invention provides a nickel-based submerged arc sintering flux for nuclear power, which is prepared from a dry powder component and a binder potassium sodium silicate in the following weight proportions: 50-60 parts by weight of fluorite, 10-20 parts by weight of sillimanite, 10-20 parts by weight of magnesia, 5-10 parts by weight of wollastonite, 5-10 parts by weight of chrome green, 1-5 parts by weight of aluminum-magnesium alloy, 1-5 parts by weight of niobium-nickel alloy, 1-3 parts by weight of metal manganese, Sodium potassium silicate 20-25 parts by weight.

[0011] The nickel-based submerged arc sintering flux for nuclear power according to the present invention is prepared from the following dry powder components and a binder potassium sodium silicate in the following weight proportions (N1): 50 parts by weight of fluorite, 14 parts by weight of sillimanite, 16 parts by weight of magnesia, 6 parts by weight of wollastonite, 8 parts by weight of chrome green, 2 parts by weight of aluminum-magnesium alloy, 2 parts by weight of niobium-nickel alloy, 2 parts by weight of metal manganese, 23 parts by weight of potassium sodium silicate.

[0012] The nickel-based submerged arc sintering flux for nuclear power according to the present invention is prepared from the following dry powder components and a binder potassium sodium silicate in the following weight proportions (N2): 56 parts by weight of fluorite, 14 parts by weight of sillimanite, 10 parts by weight of magnesia, 6 parts by weight of wollastonite, 6 parts by weight of chrome green, 3 parts by weight of aluminum-magnesium alloy, 3 parts by weight of niobium-nickel alloy, 2 parts by weight of metallic manganese, 22 parts by weight of potassium sodium silicate.

[0013] The nickel-based submerged arc sintering flux for nuclear power according to the present invention is prepared from the following dry powder components and a binder potassium sodium silicate in the following weight proportions (N3): 54 parts by weight of fluorite, 14 parts by weight of sillimanite, 12 parts by weight of magnesia, 6 parts by weight of wollastonite, 6 parts by weight of chrome green, 3 parts by weight of aluminum-magnesium alloy, 3 parts by weight of niobium-nickel alloy, 2 parts by weight of metallic manganese, 24 parts by weight of potassium sodium silicate.

[0014] The nickel-based submerged arc sintering flux for nuclear power according to the present invention is prepared from the following dry powder components and a binder potassium sodium silicate in the following weight proportions (N4): 54 parts by weight of fluorite, 16 parts by weight of sillimanite, 10 parts by weight of magnesia, 6 parts by weight of wollastonite, 6 parts by weight of chrome green, 3 parts by weight of aluminum-magnesium alloy, 3 parts by weight of niobium-nickel alloy, 2 parts by weight of metallic manganese, 23 parts by weight of potassium sodium silicate.

[0015] According to the nickel-based submerged arc sintered flux for nuclear power of the present invention, the magnesia is a mixture of sintered magnesia and fused magnesia in a ratio of 3:1. According to the nickel-based submerged arc sintered flux for nuclear power of the present invention, the potassium sodium silicate is a 2:1 high model potassium sodium silicate. According to the nickel-based submerged arc sintered flux for nuclear power of the present invention, the potassium sodium silicate is a 2:1 high model potassium sodium silicate with a Baume degree (20°C) of 48.0-49.5Be, potassium oxide of 8.5-9.5%, sodium oxide of 4.2-5.0%, and a modulus (M) of 2.8-3.0.

[0016] According to the nickel-based strip-electrode submerged arc sintering flux for nuclear power of the present invention, the particle size of the particles is 10-60 meshes, for example, 14-60 meshes.

[0017] The nickel-based strip-electrode submerged arc sintering flux for nuclear power according to the present invention is used for surfacing with the nickel-based welding strip EQNiCrFe-7A for nuclear power.

[0018] The nickel-based submerged arc sintering flux for nuclear power according to the present invention is prepared according to a method comprising the following steps: Weigh the dry powder of each material of each sintering flux according to the formula amount, put it into the dry mixer and dry mix it for 10min~15min (for example, 12min), and pour it into the wet mixer after dry mixing evenly; Add the formulated amount of potassium sodium silicate and wet mix for 5-10 minutes (e.g. 8 minutes). After the wet mix is ​​uniform, the wet powder is sent to a granulation disk through a conveyor belt for granulation. After granulation is completed, it is sent to a low-temperature drying furnace via a conveyor belt, dried at a temperature of 180-230°C (e.g. 220°C) for 30-50 minutes (e.g. 45 minutes), and then lifted by an elevator and sieved (14-60 mesh); The screened semi-finished granular flux is put into a high-temperature kiln for sintering at a high temperature of 550-600°C (for example, 580°C) for 80-100 minutes (for example, 90 minutes). After being taken out of the kiln, it is cooled, lifted, screened (with a particle size range of 10-60 meshes), and packaged to form a finished flux product.

[0019] According to the nickel-based strip-electrode submerged arc sintering flux for nuclear power of the present invention, it is used in combination with the nickel-based welding strip EQNiCrFe-7A for nuclear power for surfacing welding, and the mass fractions of the metal chemical components of the obtained surfacing layer are: C≤0.04%, Si≤0.75%, Mn≤5.0%, S≤0.008%, P≤0.015%, Cr28%~31.5%, Mo≤0.5%, Nb≤2.5%, Fe7-12%, and the balance is Ni.

[0020] According to the nickel-based strip-electrode submerged arc sintering flux for nuclear power of the present invention, it is used in combination with the nickel-based welding strip EQNiCrFe-7A for nuclear power for surfacing welding, and the mass fractions of the metal chemical components of the obtained surfacing layer are: C≤0.04%, Si≤0.5%, Mn≤4%, S≤0.008%, P≤0.01%, Cr28%~30%, Mo≤0.3%, Nb≤2.5%, Fe7-10%, and the balance is Ni.

[0021] According to the nickel-based strip-electrode submerged arc sintering flux for nuclear power of the present invention, it is used in combination with the nickel-based welding strip EQNiCrFe-7A for nuclear power for surfacing welding, and the mass fractions of the metal chemical components of the obtained surfacing layer are: C≤0.04%, Si≤0.5%, Mn2~4%, S≤0.008%, P≤0.01%, Cr29%~30%, Mo≤0.3%, Nb1.5~2.5%, Fe7-9%, and the balance is Ni.

[0022] According to the nickel-based strip-electrode submerged arc sintering flux for nuclear power of the present invention, it is used in combination with the nickel-based welding strip EQNiCrFe-7A for nuclear power for surfacing welding, and the mass fractions of the metal chemical components of the obtained surfacing layer are: C≤0.04%, Si≤0.5%, Mn2.5~3.5%, S≤0.008%, P≤0.01%, Cr29%~30%, Mo≤0.2%, Nb1.75~2.25%, Fe7.5-8.5%, and the balance is Ni.

[0023] In addition, the present invention also relates to a method for preparing the nickel-based submerged arc sintering flux for nuclear power as described in any embodiment of the present invention, comprising the following steps: Weigh the dry powder of each material of each sintering flux according to the formula amount, put it into the dry mixer and dry mix it for 10min~15min (for example, 12min), and pour it into the wet mixer after dry mixing evenly; Add the formulated amount of potassium sodium silicate and wet mix for 5-10 minutes (e.g. 8 minutes). After the wet mix is ​​uniform, the wet powder is sent to a granulation disk through a conveyor belt for granulation. After granulation is completed, it is sent to a low-temperature drying furnace via a conveyor belt, dried at a temperature of 180-230°C (e.g. 220°C) for 30-50 minutes (e.g. 45 minutes), and then lifted by an elevator and sieved (14-60 mesh); The screened semi-finished granular flux is put into a high-temperature kiln for sintering at a high temperature of 550-600°C (for example, 580°C) for 80-100 minutes (for example, 90 minutes). After being taken out of the kiln, it is cooled, lifted, screened (with a particle size range of 10-60 meshes), and packaged to form a finished flux product.

[0024] Some existing nickel-based alloys have the characteristics of poor fluidity and poor thermal conductivity, and are prone to defects such as slag sticking, undercutting, and thermal cracking during welding. The inventors adjusted the flux components and the content of each component according to the influence of the physical properties of the flux slag on the welding process performance, used high-grade raw materials, and designed a reasonable flux slag system.

[0025] The main means of ensuring the welding process performance of the present invention is to adjust the melting point, density, viscosity, tension, etc. of the slag by controlling the addition amount of metal elements and alkaline oxides to ensure the quality of the weld.

[0026] The main means to improve the mechanical properties of weld metal is to add alloy elements to the flux to ensure a reasonable ratio of alloy elements in the weld; control the basicity of the slag system to reduce the transition of silicon; improve the quality of raw materials, reduce harmful impurities in the raw materials, and improve the purity of the weld.

[0027] The flux obtained by the present invention has one or more advantages, for example, it has one or more advantages compared with the prior art: (1) By adding metal elements Mn and Mg, deoxidation is involved and slag removal performance is improved. At the same time, transition alloy elements are used to ensure the chemical composition of the cladding metal. By adding metal elements Al and Nb, solid solution strengthening and the precipitation of Ni3Al and Ni3Nb phases are promoted to strengthen the weld metal. (2) The flux of the present invention is first dried at 180-230°C to remove 99% of the moisture, and then sintered at 550-600°C. Compared with sintered flux, it not only ensures that the obtained flux has a certain strength, but also increases the transition effect of the alloy elements required for the weld metal. (3) The use of alloy compounds for composite deoxidation is easier to control the size of inclusions than a single deoxidizer, and the distribution of inclusions in the deposited metal is also more dispersed. (4) The present invention uses a variety of composite compounds to add corresponding components. During the welding process, the decomposition of the compound is mainly the breaking of chemical bonds. To break the chemical bonds that are well combined, it is necessary to absorb heat to achieve this. This can relatively reduce the heat energy during welding and reduce the possibility of thermal cracks.

[0028] Generally speaking, the flux prepared by the present invention exhibits excellent effects in one or more aspects. DETAILED DESCRIPTION

[0029] The present invention can be further described by the following examples, however, the scope of the present invention is not limited to the following examples. It will be appreciated by those skilled in the art that various changes and modifications may be made to the present invention without departing from the spirit and scope of the present invention. The present invention provides general and / or specific descriptions of the materials and test methods used in the test. Although many materials and operating methods used to achieve the purpose of the present invention are well known in the art, the present invention is still described in as much detail as possible herein. The following examples further illustrate the present invention, rather than limiting the present invention.

[0030] Example 1: Preparation of sintered flux According to the present invention, four sintering fluxes using dry powder component formulas are designed, which are numbered N1 to N4, and potassium sodium silicate (potassium sodium water glass) of specific specifications is used as a binder to prepare the sintering fluxes. The weight proportions of the dry powder components of the four sintering fluxes and the amount of water glass added (all in parts by weight, and each part by weight is calculated as 1 kg when feeding) are shown in the table.

[0031] Table 1: Flux components by weight

[0032] The magnesia used in N1~N4 flux is a mixture of sintered magnesia and fused magnesia in a ratio of 3:1; the potassium sodium silicate used has a Baume degree (20°C) of 48.0-49.5, potassium oxide of 8.5-9.5%, sodium oxide of 4.2-5.0%, and a 2:1 high model potassium sodium silicate with a modulus (M) of 2.8-3.0.

[0033] The preparation method of flux is as follows: Weigh the dry powder of each material of each sintering flux according to the formula in Table 1 (1 part by weight is equal to 1 kg), put it into the dry mixer and dry mix it for 10min~15min (12min), and pour it into the wet mixer after dry mixing evenly; Add the formulated amount of potassium sodium silicate and wet mix for 5min~10min (8min). After the wet mix is ​​uniform, send the wet powder to the granulation plate through a conveyor belt for granulation; After granulation is completed, it is sent to a low-temperature drying furnace via a conveyor belt and dried at 180-230℃ (220℃) for 30~50min (45min), then lifted by an elevator and sieved (14~60 mesh); The screened semi-finished granular flux is put into a high-temperature kiln for sintering at a high temperature of 550-600℃ (580℃) for 80-100min (90min). After leaving the kiln, it is cooled, lifted, screened (the particle size range is 10~60 mesh), and packaged to make the finished flux.

[0034] Example 2: Welding The purpose of the various fluxes prepared in Example 1 of the present invention is to use them for surfacing with nickel-based welding strip EQNiCrFe-7A for nuclear power, and the specifications of the welding strip used are 60mm×0.5mm (width×thickness).

[0035] The material of the test steel plate is 16Mn and the thickness is 40mm.

[0036] Strip electrode cladding process parameters are as follows: Current 750A, Voltage 28V, Welding speed 16.7cm / min, Stem extension 25~35mm, The overlap amount is 6~10mm.

[0037] According to the above process parameters, the nickel-based welding strip EQNiCrFe-7A for nuclear power was welded with four kinds of fluxes N1~N4 respectively. The welding process performance is shown in Table 2.

[0038] Table 2: Welding process performance of flux

[0039] The results show that although the formulas are similar, the performance of N4 flux is significantly better than the other three.

[0040] In addition, the chemical composition of the welding strip and the cladding layer metal was determined respectively. The results are shown in Table 3 below.

[0041] Table 3: Chemical composition of welding strip and cladding metal (wt.%)

[0042] As expected from the flux formulation, the results show that the proportion of manganese and niobium in the weld overlay metal is increased.

[0043] Example 3: Performance test of cladding metal The cladding metal obtained by welding with N4 flux was subjected to a bending test. The results are shown in Table 4 below.

[0044] Table 4: Bend test results of weld overlay metal

[0045] The above results show that the metal bending test results of the cladding layer obtained by welding with N4 flux are excellent.

[0046] Next, the inventors determined the intergranular corrosion sensitivity of the cladding metal obtained by welding with N4 flux according to the "Method B Copper-copper sulfate-16% sulfuric acid test" of the National Standard of the People's Republic of China GB / T 15260-94 (Test Method for Intergranular Corrosion of Nickel-Based Alloys). This method can determine the intergranular corrosion sensitivity related to the precipitation of chromium carbide or chromium nitride, and can be used to evaluate the heat treatment system of the material delivery state, the effect of adding stabilizing elements (Nb, etc.), and the improvement of intergranular corrosion resistance by reducing the content of interstitial elements, and is applicable to all forging products and weld metals. For specific operations, please refer to the national standard. The specific results are shown in Table 5.

[0047] Table 5: Metal corrosion test results of the cladding layer obtained by welding with N4 flux

[0048] In addition, the inventors have found that, as described in Example 1, by using a mixture of sintered magnesia and fused magnesia in a ratio of 3:1 as magnesia, and using a flux obtained by using a 2:1 high-model potassium sodium silicate, the N4 flux has excellent results in the metal corrosion test of the weld cladding layer obtained by welding. However, in other tests conducted by the applicant, it was found that the selection of magnesia and potassium sodium silicate has an impact on product performance. Specifically, according to Examples 1 to 3, referring to the N4 formula but replacing all the magnesia therein with sintered magnesia or all with fused magnesia, two fluxes N4a and N4b are obtained respectively, and then these two fluxes are used for welding; in the welding process performance investigation shown in Table 2, the results of the four parameters of the welding strip + N4a are medium, excellent, medium, and good, respectively, and the results of the four parameters of the welding strip + N4b are medium, excellent, general, and medium, respectively; in the weld cladding layer metal corrosion test shown in Table 5, the weld cladding layer metal corrosion test result obtained by N4a is unqualified, and the weld cladding layer metal corrosion test result obtained by N4b is unqualified. In some other experiments, according to Examples 1 to 3, referring to the N4 formula, the 2:1 high model potassium sodium silicate was changed to 1:1 low model potassium sodium silicate (Baume degree Be (20°C) 41.0-43.0, potassium oxide % = 6.0, sodium oxide % = 6.0, modulus (M) 2.5-2.7), 2:1 low model potassium sodium silicate (Baume degree Be (20°C) 43.0-44.5, potassium oxide % = 8. 5-10.0, sodium oxide % = 4.5-5.0, modulus (M) 2.5-2.7), 3:1 low model sodium potassium silicate (Baume degree Be (20℃) 43.0-44.5, potassium oxide % = 10.50, sodium oxide % = 3.50, modulus (M) 2.5-2.7), 3:1 high model sodium potassium silicate (Baume degree Be (20℃) 48.0-49.5, potassium oxide % = 11.0, sodium oxide %=3.50, modulus (M)2.8-3.0), and four kinds of fluxes N4c, N4d, N4e and N4f were obtained respectively; then these four fluxes were used for welding, and in the welding process performance inspection shown in Table 2, the results of the four parameters of the welding strip + N4c were medium, medium, good and good, the results of the four parameters of the welding strip + N4d were good, excellent, medium and good, the results of the four parameters of the welding strip + N4e were medium, good, medium and good, and the results of the four parameters of the welding strip + N4f were good, good, general and medium; in the surfacing metal corrosion test shown in Table 5, the surfacing metal corrosion test result of the surfacing metal obtained by N4c was unqualified, the surfacing metal corrosion test result of the surfacing metal obtained by N4d was unqualified, the surfacing metal corrosion test result of the surfacing metal obtained by N4e was unqualified, and the surfacing metal corrosion test result of the surfacing metal obtained by N4f was unqualified.

[0049] The above results show that selecting appropriate magnesium sand and potassium sodium silicate as feed materials is beneficial for obtaining a flux with excellent performance. The above description is only an embodiment of the present invention, and does not limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made by using the content of the present invention specification, or directly or indirectly applied in other related technical fields, is also included in the patent protection scope of the present invention.

Claims

1. A nickel-based submerged arc sintering flux for nuclear power and a preparation method thereof, which is prepared from a dry powder component and a binder potassium sodium silicate in the following weight proportions: 50-60 parts by weight of fluorite, 10-20 parts by weight of sillimanite, 10-20 parts by weight of magnesia, 5-10 parts by weight of wollastonite, 5-10 parts by weight of chrome green, 1-5 parts by weight of aluminum-magnesium alloy, 1-5 parts by weight of niobium-nickel alloy, 1-3 parts by weight of metal manganese, Sodium potassium silicate 20-25 parts by weight.

2. The nickel-based submerged arc sintering flux for nuclear power according to claim 1 is prepared from the following weight proportions of dry powder components and binder potassium sodium silicate (N1): 50 parts by weight of fluorite, 14 parts by weight of sillimanite, 16 parts by weight of magnesia, 6 parts by weight of wollastonite, 8 parts by weight of chrome green, 2 parts by weight of aluminum-magnesium alloy, 2 parts by weight of niobium-nickel alloy, 2 parts by weight of metal manganese, 23 parts by weight of potassium sodium silicate.

3. The nickel-based submerged arc sintering flux for nuclear power according to claim 1 is prepared from the following weight proportions of dry powder components and binder potassium sodium silicate (N2): 56 parts by weight of fluorite, 14 parts by weight of sillimanite, 10 parts by weight of magnesia, 6 parts by weight of wollastonite, 6 parts by weight of chrome green, 3 parts by weight of aluminum-magnesium alloy, 3 parts by weight of niobium-nickel alloy, 2 parts by weight of metallic manganese, 22 parts by weight of potassium sodium silicate.

4. The nickel-based submerged arc sintering flux for nuclear power according to claim 1 is prepared from the following weight proportions of dry powder components and binder potassium sodium silicate (N3): 54 parts by weight of fluorite, 14 parts by weight of sillimanite, 12 parts by weight of magnesia, 6 parts by weight of wollastonite, 6 parts by weight of chrome green, 3 parts by weight of aluminum-magnesium alloy, 3 parts by weight of niobium-nickel alloy, 2 parts by weight of metallic manganese, 24 parts by weight of potassium sodium silicate.

5. The nickel-based submerged arc sintering flux for nuclear power according to claim 1, which is prepared from the following weight proportions of dry powder components and binder potassium sodium silicate (N4): 54 parts by weight of fluorite, 16 parts by weight of sillimanite, 10 parts by weight of magnesia, 6 parts by weight of wollastonite, 6 parts by weight of chrome green, 3 parts by weight of aluminum-magnesium alloy, 3 parts by weight of niobium-nickel alloy, 2 parts by weight of metallic manganese, 23 parts by weight of potassium sodium silicate.

6. The nickel-based strip-electrode submerged arc sintered flux for nuclear power according to claim 1, wherein the magnesia is a mixture of sintered magnesia and fused magnesia in a ratio of 3:1; or, the potassium sodium silicate is a 2:1 high model potassium sodium silicate; or, the potassium sodium silicate is a 2:1 high model potassium sodium silicate with a Baume degree (20°C) of 48.0-49.5, potassium oxide of 8.5-9.5%, sodium oxide of 4.2-5.0%, and a modulus (M) of 2.8-3.

0.

7. The nickel-based strip-electrode submerged arc sintering flux for nuclear power according to claim 1, wherein the particle size of the flux is 10-60 mesh, for example, 14-60 mesh; or, the flux is used for surfacing with the nickel-based welding strip EQNiCrFe-7A for nuclear power.

8. The nickel-based submerged arc sintering flux for nuclear power according to claim 1 is prepared by a method comprising the following steps: Weigh the dry powder of each material of each sintering flux according to the formula amount, put it into the dry mixer and dry mix it for 10min~15min (for example, 12min), and pour it into the wet mixer after dry mixing evenly; Add the formulated amount of potassium sodium silicate and wet mix for 5-10 minutes (e.g. 8 minutes). After the wet mix is ​​uniform, the wet powder is sent to a granulation disk through a conveyor belt for granulation. After granulation is completed, it is sent to a low-temperature drying furnace via a conveyor belt, dried at a temperature of 180-230°C (e.g. 220°C) for 30-50 minutes (e.g. 45 minutes), and then lifted by an elevator and sieved (14-60 mesh); The screened semi-finished granular flux is put into a high-temperature kiln for sintering at a high temperature of 550-600°C (for example, 580°C) for 80-100 minutes (for example, 90 minutes). After being taken out of the kiln, it is cooled, lifted, screened (with a particle size range of 10-60 meshes), and packaged to form a finished flux product.

9. The nickel-based strip-electrode submerged arc sintering flux for nuclear power according to claim 1 is used in combination with the nickel-based welding strip EQNiCrFe-7A for nuclear power for surfacing, and the mass fraction of the metal chemical composition of the obtained surfacing layer is: C≤0.04%, Si≤0.75%, Mn≤5.0%, S≤0.008%, P≤0.015%, Cr28%~31.5%, Mo≤0.5%, Nb≤2.5%, Fe7-12%, and the balance is Ni; or The mass fraction of the chemical composition of the metal of the obtained cladding layer is: C≤0.04%, Si≤0.5%, Mn≤4%, S≤0.008%, P≤0.01%, Cr28%~30%, Mo≤0.3%, Nb≤2.5%, Fe7-10%, and the balance is Ni; or, The mass fraction of the chemical composition of the metal of the obtained cladding layer is: C≤0.04%, Si≤0.5%, Mn2~4%, S≤0.008%, P≤0.01%, Cr29%~30%, Mo≤0.3%, Nb1.5~2.5%, Fe7-9%, and the balance is Ni; or, The mass fractions of the chemical composition of the metal of the obtained surfacing layer are: C≤0.04%, Si≤0.5%, Mn2.5~3.5%, S≤0.008%, P≤0.01%, Cr29%~30%, Mo≤0.2%, Nb1.75~2.25%, Fe7.5-8.5%, and the balance is Ni.

10. The method for preparing the nickel-based submerged arc sintering flux for nuclear power according to any one of claims 1 to 9, comprising the following steps: Weigh the dry powder of each material of each sintering flux according to the formula amount, put it into the dry mixer and dry mix it for 10min~15min (for example, 12min), and pour it into the wet mixer after dry mixing evenly; Add the formulated amount of potassium sodium silicate and wet mix for 5-10 minutes (e.g. 8 minutes). After the wet mix is ​​uniform, the wet powder is sent to a granulation disk through a conveyor belt for granulation. After granulation is completed, it is sent to a low-temperature drying furnace via a conveyor belt, dried at a temperature of 180-230°C (e.g. 220°C) for 30-50 minutes (e.g. 45 minutes), and then lifted by an elevator and sieved (14-60 mesh); The screened semi-finished granular flux is put into a high-temperature kiln for sintering at a high temperature of 550-600°C (for example, 580°C) for 80-100 minutes (for example, 90 minutes). After being taken out of the kiln, it is cooled, lifted, screened (with a particle size range of 10-60 meshes), and packaged to form a finished flux product.

Citation Information

Patent Citations

  • Sintered flux for nickel-based band electrode submerged-arc welding

    CN104722956A

  • Sintered flux for nickel-based strip submerged arc welding

    CN104722956B

  • Nickel-based strip electrode submerged overlaying welding sintered flux and preparation method

    CN105215576A

  • Preparation method for sintered flux used for nickel base strip electrode submerged arc surfacing

    CN105252172A

  • Sintered flux for band electrode submerged arc surfacing of nickel-based 625 alloy and preparation method of sintered flux

    CN106514054A